Investigating the Causal Link between Rheumatoid Arthritis and Atrial Fibrillation in East Asian Populations: A Mendelian Randomization Approach - Weijun Luo; Hui Yv; Xiao Yu; Xianjun Wu (Cardiology Research and Practice)
Background. Rheumatoid arthritis (RA) has been associated with atrial fibrillation (AF) in observational studies, yet the causal relationship remains elusive. In this study, we employed Mendelian randomization (MR) to investigate the impact of RA on AF risk specifically in East Asian populations. Methods. Utilizing genome-wide association study (GWAS) data on RA (n = 212,453) and AF (n = 36,792), we applied the following five MR methods: inverse variance weighted (IVW), MR-RAPS, maximum likelihood, weighted median (WM), and Bayesian weighted Mendelian randomization (BWMR). We evaluated heterogeneity, sensitivity, and pleiotropy. Results. Five genetic instrumental variants for RA were identified. All MR methods consistently indicated a causal association between RA and AF (IVW: OR = 1.20, 95% CI: 1.01–1.41, p<0.03; MR-RAPS: OR = 1.21, 95% CI: 1.03–1.42, p<0.02; maximum likelihood: OR = 1.20, 95% CI: 1.04–1.39, p<0.01; WM: OR = 1.25, 95% CI: 1.03–1.52, p<0.03; and BWMR: OR = 1.20, 95% CI: 1.02–1.42, p<0.03). Sensitivity and pleiotropy analyses confirmed the robustness and validity of the results. Conclusions. This study establishes a causal link between RA and AF in East Asians. Our results underscore the need for in-depth mechanistic investigations to unravel the underlying pathways. Clinicians should consider AF risk in RA management, emphasizing collaborative care between rheumatologists and cardiologists. Moving forward, future research should explore therapeutic interventions and address the shared biological mechanisms.